Implementasi Moderasi Beragama dalam Mencegah Faham Radikalisme dan Intoleran di Kampung Kristen Bojonegoro - Habibi, Ibnu (Proceedings of Annual Conference for Muslim Scholars, 2022)
: Religious moderation is very much needed in the life of today's nation. Along with the emergence of extreme religious beliefs that have threatened harmony in social life so that it can lead to the notion of radicalism and intolerance between religious communities which leads to the division of the unity of the Republic of Indonesia. This study aims to describe the implementation of religious moderation in preventing radicalism and intolerance in the Kampung Kristen of Leran Village, Kalitidu District, Bojonegoro Regency. This research is a field research with a qualitative approach and developed with an inductive method in order to understand the social situation in depth and find a pattern of relationships between findings in the field, then formulate hypotheses and draw conclusions. Data collection techniques by observation, interviews and documentation. Sources of data are also obtained from primary data and secondary data. Primary data is data obtained directly from field research. And secondary data is data obtained by researchers indirectly through data from documentation or other results. The results of this study indicate that the community of Kampung Kristen has implemented several principles of Religious Moderation which include; tawasut (taking the middle way), tawazun (balance), tasamuh (tolerant), Musawah (egalitarian), shura (deliberation), and tathawwur wa ibtikar (dynamic and innovative). This is shown by the existence of RT deliberations, village deliberations, village community service, attending tahlil, and attending activities carried out by Christians when invited, there is an agreement between the three religious sects, mutual awareness, mutual respect, being kind, keeping existing problems. In the community so that other people don't know. This is what makes Christian Villages able to prevent radicalism and intolerance so that life becomes safe, peaceful and serene.